LEGAL CHALLENGES OF THE CROATIAN LEGISLATURE WITH REGARD TO THE HATE SPEECH AND COMMITTING CERTAIN CRIMINAL OFFENSES - Dagen, Tomislav (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
A man’s perennial desire and struggle for freedom of speech, freedom of expression, will experience the paradigm and reality in today’s time, despite the evolutionary development of such desire and struggle in relation to power and the legislator who will eventually articulate these desires. Freedom of expression is the highest human, social and humanistic evolutionary value in liberal democracy in which an individual or group of people can convey their own views, thoughts and criticisms to other people, groups and the governing structure. Unfortunately, freedom of expression in the 1920s began to demonstrate the dysfunction and anomalies of such values ​​in public, media space, especially through electronic media, electronic publications, through modern electronic platforms, which are accessible by a large number of people. In concrete terms, and considering the Croatian reality(ies) and experience with the above-mentioned phenomenon, it is indisputable that we are witnessing the abuse or misunderstanding of the limits of freedom of expression which, due to extensive interpretation or misunderstanding of democracy, radicalizes and abuses freedom of expression. The emergence of abuse of freedom of expression results in hate speech and the commission of certain crimes (public incitement to terrorism, terrorism, public incitement to violence and hatred). Thus, we can say that there is a(n) (in)direct link between the freedom of expression provided for in Articles 9 and 10(1) of the European Convention for the Protection of Human Rights and Fundamental Freedoms and other constitutional and legal provisions of the Republic of Croatia. The abuse of the exercise of these rights results in commission of certain criminal offenses. Although hate speech and the radicalization of the media space through new electronic platforms have disavowed freedom of speech and opinion, it has also raised the question of the sufficiency of the existing legislative framework and the need for a new legislative response (example of Austrian counter-terrorism measures) with which, as a new form of legal struggle, these phenomena would be prevented and sanctioned. All of the above poses a legal challenge of existing constitutional provisions and the legislative framework in Croatia. Having this in mind, should Croatian legislator follow the example of the Austrian legislator and respond to abuses and violations of freedom of expression. Recognizing the above phenomena and connections between the abuse of freedom of expression with the commission of certain criminal offenses, the author uses scientific analysis and comparative method to examine the legal challenges and/or the strength of the Croatian legislative framework and asks whether there are perhaps new legal mechanisms that should be a response to these phenomena in order to further strengthen and protect the of freedom of expression.
Keywords: hate speech, freedom of expression, public incitement to terrorism, terrorism, incitement to violence and hat